INSĀN CHARACTER FROM THE PERSPECTIVE OF THE KORAN - Fahrurozi Umiari; Ahmad Syukron; Ade Nailul Huda (Jurnal Pendidikan Karakter JAWARA (Jujur, Adil, Wibawa, Amanah, Religius, Akuntabel), 2026)
Insān are the most dominant creatures on earth. Philosophy and science have used various methods to understand him, but he is only able to know certain aspects of the person, he does not know the whole person, even most of the questions asked by those who study the insān -to themselves- still remain unanswered. Therefore, one of the ways to know who the human is to refer to divine revelation so that we can find the answers. For this reason, this study aims to find out about the insān as well as its characteristics from the perspective of the Koran. This research uses the mauḍū'ī (thematic) tafsir method. The results show that what is meant by insan in the Koran is a human being with all his totality, body and soul. The Koran mentions many characteristics of insan -from positive to negative-, and these characteristics can be classified into two: Inborn (fiṭrī) and acquired (muktasab). The innate characters (fiṭrī) described by the Quran are: Weak, hasty, fond of arguing and disputing, miserly, restless and complaining, unjust and ignorant, transgressing limits, very insubordinate, happy, boast. As for the acquired character (muktasab) which is pursued by the insān himself, among others: Kufr, disobedience, quarrel, despair, and hopelessness.